Amplitude de distribuição do diâmetro dos eritrócitos (RDW), volume corpuscular médio e reticulócitos em gato doméstico hígido (Felis catus Linnaeus, 1758) - Silva, Paulo Henrique da (2013)
Changes in the results of erythrocyte standards require decisions and guide the conduct of clinical regarding prognosis and treatment of any diseases. The use of modern equipment that make the blood cell count used to calculate the RDW (red cell distribution width) and its fractions RDW-CV and RDW-SD, which provide a quantitative assessment of heterogeneity of each erythrocyte. Given the limited information available in the literature about the RDW for the domestic cat, this study aims to compare the values of RDW, with MCV and reticulocytes from 40 (n=14males, n=26 females) healthy mongrel cats, with age ranging from 1.2 to 5.5 years (3.0 ± 1.2) were used. The animals were kept in individual cages all over the experiment. Blood samples were taken directly from the external jugular vein and separated into two tubes: one containing anticoagulant EDTA (ethylene diamine tetra acetic acid) to 10% for the complete blood count and the second without anticoagulant for biochemical tests. The results showed that there is a direct relationship between values of RDW-SD and RDW-CV and an inverse correlation between RDW-CV with MCV. There was no relation between RDW and reticulocyte aggregates or punctate. There was no relation between sex and RDW as well. RDW values determined in this experiment can be used as a resource for future research and also as reference values for the feline species.